PERADILAN TATA USAHA NEGARA DALAM KONTEKS UNDANG-UNDANG NO. 30 TH. 2014 TENTANG ADMINISTRASI PEMERINTAHAN - Hadjon, Philipus M (Jurnal Hukum dan Peradilan, 2015)
Act No. 30 Year 2014 on Government Administration (UU AP) instead of administrative law. The concept of public administration (AP) in Article 1.1 is governance in the decision and / or action by the official agency and / or government. When compared with the Dutch Algemene wet Bestuursrecht (AWB), it seems obvious differences. AWB moved from the concept of administrative law (bestuursrecht) while the AP is the starting point of governmentÂ  dministration. That in AP there are aspects of administrativeÂ  law, but the concept of administrative law is confusing. On the basis, the common explanations of AP stating AP Act is a substantive law of the State Administrative Court system becomes a big question mark. AP Act provisions concerning Administrative Court is not based on a clear conceptual approach. On the basis, AP Act concerning Administrative Court is very difficult to apply in judicial practice as well as vague concepts is also contrary to the concepts of administrative law. Keywords: Judicial, Administrative Court, Act No. 30 Year 2014 on Government Administration